Real-time optical information processing - Javidi, Bahram; Horner, Joseph L. (Joseph LeFevre) (Academic Press, 1994)
Real-Time Optical Information Processing covers the most recent developments in optical information processing, pattern recognition, neural computing, and materials for devices in optical computing. Intended for researchers and graduate students in signal and information processing with some elementary background in optics, the book provides both theoretical and practical information on the latest in information processing in all its aspects. Leading researchers in the field describe the significant signal processing algorithms architectures in optics as well as basic hardware concepts, such as the fundamentals of spatial light modulators. Each chapter begins with a review of basic concepts and follows with a discussion of recent advances in the field. A complete bibliography on the fundamentals of each topic is also included to aid the reader. Contributors are among the leading researchers in the area Chapters begin with reviews of basic concepts Complete bibliographical information is included.